Local Government Sick-Leave Practices: An Exploratory Study. (December 2017) - Reilly, Thom; Thom, Michael
The purpose of this study was to examine paid sick leave (PSL) practices among large municipal governments in the United States. Results of a national survey suggest that over 90% of these governments offer PSL. Few reported making any post-recession changes, and in fact, most governments continue to allow employees to rollover unused sick leave from year to year, cash out unused sick leave upon termination, and/or include unused sick leave in pension calculations despite the sometimes significant cost of such policies. Documentation is required in 70% of governments, but formal auditing of PSL occurs in less than one third of responding governments. Type of government, employee classification (e.g., public safety vs. general staff), collective bargaining, and whether the government requires public hearings for public employee benefit changes were significant factors in determining certain PSL practices.